Energy efficiency in small and medium scale foundry industry - G. Patange; M. Khond (Metalurgija, 2016)
In this paper, the research results of surveys which were conducted in an Indian foundry cluster which are potential members of such sectors are presented. These results indicate that there is an enough potential improvement in the energy use. The use of energy efficient practices can result in their energy use effectively as well as cost reduction. The key findings about the energy pattern are a lack of energy efficient practices. The suggested recommendations can contribute to an increase in energy efficiency in such cluster.